Developing Multitier Open-ended Transverse Wave Instrument (MOTWI): How to Assess Students' Misconceptions? - Mufida, Shobrina Nurul; Kaniawati, Ida; Samsudin, Achmad; Suhendi, Endi; Aminudin, Adam Hadiana; Umar, Fini Alfionita; Astuti, Itsna Rona Wahyu; Kunaedi, Jajang; Dewi, Fanny Herliyana (KnE Social Sciences, 2024)
At school, students have studied the characteristics of waves and the relationship between period, frequency, wavelength, and the speed of propagation of transverse waves. However, students often experience misconceptions based on intuitive thinking and the phenomena they encountered. Thus, the research aims to describe the instrument validation of developing a multitier open-ended transverse wave instrument (MOTWI), which is useful in deeply assessing the misconceptions of high school students. The 4D (defining, designing, developing, and disseminating) model has been utilized as the method for developing the instrument. The participants were 67 high school students aged between 16 and 18 years (21 males namely “Mas” and 46 females namely “Mba”). The validity and reliability of MOTWI were analyzed using Rasch Model with MINISTEP 4.7.0.0 software. MOTWI validity from item dimensionality was valid. Cronbach Alpha (α) value was 0.75 (good category), and item reliability was a very good category. The construct validation results of MOTWI were valid and reliable for seven items. The students’ conceptions and misconceptions were analyzed with Wright maps. The conceptions of students were categorized as sound understanding (SU), partial understanding positive (PUP), partial understanding negative (PUN), no understanding (NU), misconception (MC), and no oding (NC). The misconceptions were mostly found in the characteristics and the factors that affect the speed of propagation of transverse waves. In conclusion, developing MOTWI can be used to assess and identify conceptions and misconceptions of students. Keywords: Multitier Open-ended Transverse Wave Instrument, students’ misconceptions